Pathological complete response due to a prolonged time interval between preoperative chemoradiation and surgery in locally advanced rectal cancer: analysis from the German StuDoQ|Rectalcarcinoma registry - Sven Lichthardt; Johanna Wagner; Stefan Löb; Niels Matthes; Caroline Kastner; Friedrich Anger; Christoph-Thomas Germer; Armin Wiegering (BMC Cancer, 2020)
Abstract Background Preoperative chemoradiotherapy is the recommended standard of care for patients with local advanced rectal cancer. However, it remains unclear, whether a prolonged time interval to surgery results in an increased perioperative morbidity, reduced TME quality or better pathological response. Aim of this study was to determine the time interval for best pathological response and perioperative outcome compared to current recommended interval of 6 to 8 weeks. Methods This is a retrospective analysis of the German StuDoQ|Rectalcarcinoma registry. Patients were grouped for the time intervals of “less than 6 weeks”, “6 to 8 weeks”, “8 to 10 weeks” and “more than 10 weeks”. Primary endpoint was pathological response, secondary endpoint TME quality and complications according to Clavien-Dindo classification. Results Due to our inclusion criteria (preoperative chemoradiation, surgery in curative intention, M0), 1.809 of 9.560 patients were suitable for analysis. We observed a trend for increased rates of pathological complete response (pCR: ypT0ypN0) and pathological good response (pGR: ypT0-1ypN0) for groups with a prolonged time interval which was not significant. Ultimately, it led to a steady state of pCR (16.5%) and pGR (22.6%) in “8 to 10” and “more than 10” weeks. We were not able to observe any differences between the subgroups in perioperative morbidity, proportion of rectal extirpation (for cancer of the lower third) or difference in TME quality. Conclusion A prolonged time interval between neoadjuvant chemoradiation can be performed, as the rate of pCR seems to be increased without influencing perioperative morbidity.